2013
DOI: 10.1111/1365-2745.12181
|View full text |Cite
|
Sign up to set email alerts
|

Community assembly by limiting similarity vs. competitive hierarchies: testing the consequences of dispersion of individual traits

Abstract: Summary1. The degree of dispersion of trait values among species in a community has frequently been used to infer processes of community assembly. However, multiple assembly processes can lead to the same pattern of trait dispersion or the same process can lead to different patterns of dispersion. In particular, competitive processes can lead both to trait overdispersion (if the trait controls niche differentiation and only substantial differences allow coexistence) or to trait underdispersion (if the trait co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 61 publications
8
88
0
1
Order By: Relevance
“…Root tissue density was negatively related to root system size, suggesting a common link with growth rate (Ryser 1996;Kramer-Walter et al 2016). This finding is in agreement with other studies showing that large plant size and acquisitive traits in the leaf economics spectrum translate into high competitive ability (Goldberg and Landa 1991;Keddy et al 2002;Herben and Goldberg 2014). However, we found that size-related root traits were not related to the ability to tolerate competition (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Root tissue density was negatively related to root system size, suggesting a common link with growth rate (Ryser 1996;Kramer-Walter et al 2016). This finding is in agreement with other studies showing that large plant size and acquisitive traits in the leaf economics spectrum translate into high competitive ability (Goldberg and Landa 1991;Keddy et al 2002;Herben and Goldberg 2014). However, we found that size-related root traits were not related to the ability to tolerate competition (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…strongly related to competitive hierarchies than to niches (Kunstler et al 2012;Herben and Goldberg 2014;Kraft et al 2015). This apparent contradiction highlights the current lack of a mechanistic understanding of the way in which easily measured traits relate to plant function and the way in which different traits contribute to competitive hierarchies versus niche differentiation between species (Kraft et al 2015;Shipley et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intransitive competition and competitive hierarchies are important drivers of coexistence and biodiversity in nonfungal communities [e.g., grassland plant communities (16,38)]. Nevertheless, an important outstanding question is whether or not these results extend to other systems.…”
Section: Ecologymentioning
confidence: 99%
“…Historically, colonization has been reported as the main determinant of community succession, with species showing a tradeoff between traits that favor dispersal and persistence (Herben and Goldberg, 2014;Ricklefs, 1987). Species with high dispersal ability can colonize recently created or remote habitats, causing species occupancy to become a dynamic process in biological communities (Hanski and Ovaskainen, 2000).…”
Section: Introductionmentioning
confidence: 99%